ARBOREAS VOCES SOLIS LUNEQUE LOQUENTES: ALEXANDER THE GREAT’S VISIT TO THE TREES OF THE SUN AND THE MOON IN XIITH CENTURY CHRONICLES. - De Toro Vidal, José Miguel (Revista de Historia Social y de las Mentalidades, 2016)
Alexander the Great’s encounter with the  talking trees of the Sun and the Moon in a  sacred forest of India is one of the many  fantastic episodes of his legend. The aim of  this paper is to study the moment when the  chroniclers decide to include this passage in  their works, and to inquire into the reasons for  this decision. To do so, we have examined the  universal chronicles of the 12th and early 13th  centuries, together with others works produced  at the time. We can observe that the Historia  Scholastica of Peter Comestor and the World  maps contributed to the acceptance of the  episode. However, the inclusion of this passage  is not an assertion of Alexander’s encounter  with the trees as a true historical fact, but  responds to the historical and literary project  planned by the author of each chronicle.
Keywords: Universal chronicles; Alexander the Great; India; wonders; World maps